Different oxidation treatments on polystyrene (PS) microspheres by using an ultraviolet/ozone (UVO3) system - Mel, Maizirwan; Arifin, Mohd Azmir; Samsudin, Nurhusna; Hashim, Yumi Zuhanis Has-Yun; Mohd. Salleh, Hamzah (2015)
This study investigated the effects of oxidation of polystyrene (PS) microspheres by three different treatments namely oxidation by ozone aeration only, UV irradiation only or by the combination of both (UV/O3), by using a self fabricated UV/O3 system. Results expressed in carboxylic acid functional group concentrations on the surface of microspheres revealed that treatment by UV/O3 yielded the highest concentration due too the activation of surface of PS microspheres by UV irradiation facilitated the oxidation by ozone which deposited carboxylic acid functional groups on the surface of microspheres.